Які вірування закладені в основу «Балади про замуровану наречену» (до історії тлумачення) - Стоянович, Л. (Народна творчість та етнографія, 2009)
After continual, and in folkloristcs well established interpretation of the ballad as a reminiscence of the rite of sacrifice, in the last decades of the 20th centuty, different interpretations have occurred with an attempt to change the foundation of the ballade’s source. The Christian and gender oriented reading of this ballad appeared in a similar context. The possible feministinspired interpretation and the additional male reading of the ballad offer two different perspectives: one would refer to the female victim, that is to the wall-up the wife, and the second one would refer to the male builder. It is obvious that it depends on whose story the ballad is telling about. Is it the female victim’s point of view, or is it the story about the tragic fate of the male builder widower? In any event, perhaps, neither the female nor the male interpretation may be deemed valid, but they are surely a welcome alternative to the simplistic, literal myth-ritual building sacrifice theory that has dominated the scholarship devoted to this ballad up to the end of 20th century.